Analisis Kinerja Keuangan Perusahaan Sebelum dan Sesudah Akuisisi pada Perusahaan yang Terdaftar di BEI - Deni Purnomo (2023)
This research aims to examine the differences in the financial performance of companies before and after an acquisition. The sample used consists of companies listed on the Indonesia Stock Exchange that underwent acquisitions between 2017 and 2021, with a total of 48 companies. The financial performance of these companies was observed one year before and one year after the acquisition. The sampling technique employed was purposive sampling. The variables examined included liquidity ratios (Current Ratio), activity ratios (Total Asset Turnover), solvency ratios (Long Term Debt Equity Ratio), and profitability ratios (Return On Assets). The analysis technique used was the Wilcoxon Signed-Ranks Test. The research findings indicated no significant differences in the four ratios examined: liquidity ratio, activity ratio, solvency ratio, and profitability ratio before and after the acquisition.